1986
DOI: 10.1084/jem.163.6.1566
|View full text |Cite
|
Sign up to set email alerts
|

An antigen receptor-driven, interleukin 2-independent pathway for proliferation of murine cytolytic T lymphocyte clones.

Abstract: Proliferation of T lymphocytes can be induced by IL-2, either through an autocrine pathway in which the responding cell produces its own IL-2 or through an exocrine pathway in which IL-2 secreted by Th stimulates proliferation of IL-2-dependent CTL. However, proliferation of at least some CTL clones, such as CTL L3 and CTL dB45, also can be induced by stimulation of the antigen receptor in the absence of IL-2. Stimulation of these cloned CTL with T cell-depleted allogeneic spleen cells, allogeneic tumor cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The dogma on the induction of Lyt 2 cytotoxic T cell responses in vitro clearly implicates L3T4 (Lyt 1) helper cells as providing the necessary signals for activating cytotoxic T lymphocyte precursors to their aggressor status (Cantor & Boyse, 1975;Wagner & Rollinghoff, 1978). Other groups have demonstrated departures from this dogma and have suggested that Lyt 2 cells provide their own source of 'helper' factors, or else receive induction signals from other cells (Andrus et al, 1981 ;Mizuochi et al, 1985;Moldwin et al, 1986;Sprent & Schaefer, 1986). Whatever the mechanism involved in Lyt 2 cell activation, it is clear that a deficiency in L3T4 cells actually leads to an augmented cytotoxic T cell response to this virus.…”
Section: Discussionmentioning
confidence: 99%
“…The dogma on the induction of Lyt 2 cytotoxic T cell responses in vitro clearly implicates L3T4 (Lyt 1) helper cells as providing the necessary signals for activating cytotoxic T lymphocyte precursors to their aggressor status (Cantor & Boyse, 1975;Wagner & Rollinghoff, 1978). Other groups have demonstrated departures from this dogma and have suggested that Lyt 2 cells provide their own source of 'helper' factors, or else receive induction signals from other cells (Andrus et al, 1981 ;Mizuochi et al, 1985;Moldwin et al, 1986;Sprent & Schaefer, 1986). Whatever the mechanism involved in Lyt 2 cell activation, it is clear that a deficiency in L3T4 cells actually leads to an augmented cytotoxic T cell response to this virus.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥ gene expression during CD4 ϩ T cell activation is mediated by signals transduced through the TCR, IL-12R, and/or IFN-␥R (20,36,37). Th1 maturation involves IFN-␥-mediated phosphorylation of STAT1, which in turn up-regulates expression of the T-bet transcription factor (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…A costimulatory signal was not always required for induction of T cell proliferation in response to TCR stimulation, as shown in this study and others (6,10). However, it has not been clarified why some T cells were proliferative in response to the CD3-dependent signal alone.…”
Section: Discussionmentioning
confidence: 53%
“…Although some CTLs produce IL-2, most other CTLs that do not produce IL-2 require exogeneous IL-2 for proliferation. However, some CTL clones were shown to proliferate in response to antigenic cells, anti-CD3 monoclonal antibodies (aCD3) (10) or phorbolester 12-myristate 13-acetate (PMA) (6) without production of IL-2. It has not been clarified why these CTLs proliferate in response to TCR stimulation independently of costimulatory cells or IL-2.…”
mentioning
confidence: 99%